Positive supercoiling favors transcription elongation through lac repressor-mediated DNA loops. Issue 5 (21st February 2022) - Xu, Wenxuan; Yan, Yan; Artsimovitch, Irina; Dunlap, David; Finzi, Laura
Abstract: Some proteins, like the lac repressor (LacI), mediate long-range loops that alter DNA topology and create torsional barriers. During transcription, RNA polymerase generates supercoiling that may facilitate passage through such barriers. We monitored E. coli RNA polymerase progress along templates in conditions that prevented, or favored, 400 bp LacI-mediated DNA looping. Tethered particle motion measurements revealed that RNA polymerase paused longer at unlooped LacI obstacles or those barring entry to a loop than those barring exit from the loop. Enhanced dissociation of a LacI roadblock by the positive supercoiling generated ahead of a transcribing RNA polymerase within a torsion-constrained DNA loop may be responsible for this reduction in pause time. In support of this idea, RNA polymerase transcribed 6-fold more slowly through looped DNA and paused at LacI obstacles for 66% less time on positively supercoiled compared to relaxed templates, especially under increased tension (torque). Positive supercoiling propagating ahead of polymerase facilitated elongation along topologically complex, protein-coated templates.